The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1128/aem.02102-16
|View full text |Cite
|
Sign up to set email alerts
|

Novel Capsular Polysaccharide Loci and New Diagnostic Tools for High-Throughput Capsular Gene Typing in Streptococcus suis

Abstract: Streptococcus suis is an important pathogen of pigs and may cause serious disease in humans. Serotyping is an important tool for detection and epidemiological studies of S. suis. Thirty-three reference serotypes and nine novel cps loci (NCLs) are recognized in S. suis. To gain a better understanding of the prevalence and genetic characteristics of NCLs, we investigated the serotype identity of 486 isolates isolated between 2013 and 2015 in China by capsular gene typing methods. Two hundred seventy-six isolates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
36
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(42 citation statements)
references
References 30 publications
2
36
0
Order By: Relevance
“…showed that eight lung isolates belonged to NCL1, NCL3, NCL4 and NCL11, indicating that these strains might be virulent. Further, they also demonstrated that isolates belonging to NCL1, NCL3, NCL4, NCL11 and Chz were prevalent in swine population in China and therefore, suggested increasing the surveillance on these NCLs‐harboured isolates (Qiu et al., ). Zheng et al.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…showed that eight lung isolates belonged to NCL1, NCL3, NCL4 and NCL11, indicating that these strains might be virulent. Further, they also demonstrated that isolates belonging to NCL1, NCL3, NCL4, NCL11 and Chz were prevalent in swine population in China and therefore, suggested increasing the surveillance on these NCLs‐harboured isolates (Qiu et al., ). Zheng et al.…”
Section: Discussionmentioning
confidence: 99%
“…Isolates were identified as S. suis strains by the presence of S. suis ‐specific genes recN and gdh (Ishida et al., ; Okwumabua, O'Connor, & Shull, ), and then were further confirmed by 16S rRNA sequence. PCR assays were used to identify the 29 serotypes (Liu et al., ), NCL1‐8 (Zheng et al., ), NCL9‐16 (Qiu et al., ), NCL17‐20 (Zheng et al., ) and Chz (Pan et al., ). The isolates that were non‐typeable by PCR assays were selected for further research.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, high-throughput capsular gene typing systems based on serotype-specific wzy genes have become attractive alternatives/complement to the existing serological tests [ 18 , 20 , 21 ]. However, even with the use of multiplex PCR tests, non-serotypeable strains are still commonly isolated from both clinically healthy and diseased animals [ 18 , 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, 17 novel cps loci (NCLs) were identified from non-serotypeable S. suis and were designated as NCL1 to 16 and serotype Chz [ 22 24 ]. Meanwhile, an 18-plex Luminex assay was also developed to detect these 17 NCLs and nearly 60% of non-serotypeable strains from healthy pigs carried one of these NCLs [ 22 ]. However, little is known about the distribution and characteristics of the cps loci of potentially virulent non-serotypeable strains recovered from diseased animals.…”
Section: Introductionmentioning
confidence: 99%